PERSEPSI MAHASISWA AKUNTANSI TERHADAP PENYUSUNAN LAPORAN KEUANGAN - Kurniasari, Dian (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
One of the goals of accounting education in Indonesia is to introduce the students to the ethics and values of accounting profession. This research focused on the effectiveness of acconting curiculum in developing students responsibility towards the financial statementâs users. We find that different ethics influence to perception the financial statement.